Parenting as political resistance: Disability and “dealing with” late-modern medicine - Brock, Brian (Review and expositor, 2015)
Mental disability exposes in an especially acute manner some important deficiencies in modern healthcare practices. This paper offers an account of the reasons why the deviation of the disabled from the statistical norm creates such problems for modern medical expertise. Contemporary medical science exhibits features of modern techniques and mindsets which are characteristic of late-modernity and deeply shape a wide range of human-creature interactions. I By fleshing out how this modern adherence to a suite of techniques shapes the configurations of medical knowledge a better understanding of the difficulties the mentally disabled face in modern healthcare settings will emerge. Substantiating this analysis by way of a recent empirical study the paper will propose some of the strategies for a caring resistance to these problems such an analysis might suggest to Christians today. The analysis as a whole indicates why solidarity with the disabled in the modern developed world draws Christians into various forms of political resistance to the powers of the age.